Effectiveness of a hybrid closed-loop system for children and adolescents with type 1 diabetes during physical exercise: A cross-sectional study in real life - Ruben Martin-Payo; Maria del Mar Fernandez-Alvarez; Rebeca García-García; Ángela Pérez-Varela; Shelini Surendran; Isolina Riaño-Galán (Elsevier, 2024)
Objective: The aim of the study was to describe how physical exercise affects metabolic control, insulin requirements and carbohydrate intake in children who use hybrid closed-loop systems. Methods: Cross-sectional study design. The sample included 21 children and adolescents diagnosed with type 1 diabetes. During the study, participants were monitored for a period of 7 days to gather comprehensive data on these factors. Results: Nine participants (42.9%) had switched to exercise mode to raise the target glucose temporarily to 150 mg/dL. The HbA1c values ranged from 5.5% to 7.9% (median, 6.5%; IQR, 0.75). The percentage of time within the target range of 70−180 mg/dL was similar; however, there was an increased duration of hyperglycaemia and more autocorrections on exercise days. The time spent in severe hyperglycaemia (>250 mg/dL) increased by 2.7% in exercise compared to non-exercise days (P = .02). It is worth noting that hypoglycaemic episodes did not increase during the exercise days compared with non-exercise days. Conclusion: The hybrid closed-loop system was effective and safe in children and adolescents with type 1 diabetes during the performance of competitive sports in real life. Resumen: Objetivo: El objetivo de este estudio es describir cómo el ejercicio físico afecta el control metabólico, las necesidades de insulina y el consumo de carbohidratos en niños usuarios de un sistema híbrido de circuito cerrado. Métodos: Diseño de estudio transversal. Se reclutaron veintiún niños y adolescentes diagnosticados con diabetes tipo 1. Durante el estudio, los participantes fueron monitoreados durante un período de 7 días para recopilar datos completos sobre estos factores. Resultados: Nueve participantes (42,9%) habían activado el modo de ejercicio, para elevar temporalmente la glucosa objetivo a 150 mg/dL. La HbA1c osciló entre 5,5% y 7,9% (mediana 6,5%, IQR 0,75). El porcentaje de tiempo dentro del rango de 70−180 mg/dL fue similar; sin embargo, hubo una mayor duración de la hiperglucemia y más autocorrecciones en los días en que se realizó ejercicio. El porcentaje de tiempo en hiperglucemia grave (>250 mg/dL) fue 2,7 mayor durante el ejercicio versus los días sin ejercicio (p = 0,02). En particular, los episodios de hipoglucemia no aumentaron durante los días de práctica de ejercicio, en comparación con los días sin ejercicio. Conclusiones: El sistema híbrido de circuito cerrado fue efectivo y seguro en niños y adolescentes diagnosticados con diabetes tipo 1 durante ejercicios físicos competitivos en la vida real.